The Relationship Between Health Promotion and Community Participation in the Success of Community-Based Total Sanitation Programs - Sanjaya, Mira Husni; Tondong, Henrietta Imelda; Montolalu, Ivan Adrian (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
This study explores the relationship between health promotion and community participation in the success of community-based total sanitation (CBTS) programs. Using a qualitative literature review approach, the research analyzes various studies and reports that highlight the role of health education and community involvement in ensuring the effectiveness of CBTS initiatives. The findings suggest that health promotion strategies, which focus on raising awareness and changing behaviors regarding sanitation, significantly contribute to community engagement and the sustainability of sanitation practices. Furthermore, active participation of local communities in the planning, implementation, and monitoring of sanitation programs leads to a more successful adoption of sanitation behaviors and long-term improvements in public health. The study emphasizes the importance of a collaborative approach between health professionals, local governments, and communities in achieving sustainable sanitation outcomes.